Maternal serum ischemia-modified albumin (IMA), total-sulphydryl concentrations, and some subclinic inflammatory markers in hyperemesis gravidarum (HG) - Kazım Uçkan; Halit Demir; Canan Demir (Elsevier, 2023)
Objective: This study investigates the relationship between Ischemia Modified Albumin and Total-Sulphydryl levels with some subclinical inflammatory markers in patients with hyperemesis gravidarum. Materials and methods: A total of 258 pregnant women, 137 with hyperemesis gravidarum and 121 low-risk pregnancies, were included in this case-control study. The patients were divided into three groups according to the severity of hyperemesis gravidarum as mild (n = 53), moderate (n = 41) and severe (n = 43). Results: Serum Ischemia Modified Albumin levels were statistically different from the control group (P < 0.001). Among the subgroups, the highest Ischemia Modified Albumin value was observed in the severe hyperemesis gravidarum group, and the highest Total-Sulphydryl level was observed in the mild hyperemesis gravidarum group (P < 0.001). Serum potassium levels were higher in the control group (P < 0.001). While a negative correlation was observed between Ischemia Modified Albumin and Total-Sulphydryl, a positive correlation was observed in Platelet crit, C-reactive protein, and ketonuria. As the severity of the disease increases, Ischemia Modified Albumin, which is an oxidative stress factor, increases, and Total-Sulphydryl levels decrease (p < 0.001). Logistic regression analysis revealed that a one-unit increase in Ischemia Modified Albumin resulted in a statistically significant 1.9-fold increase in the risk of Severe hyperemesis gravidarum (OR 1.92, 95% CI 1.008-1.956; P = 0.01) Conclusion: This study shows that there is a condition in the pathophysiology of hyperemesis gravidarum, with an increase in Ischemia Modified Albumin and a decrease in Total-Sulphydryl levels, and oxidative stress occurs. It was important to detect increased Ischemia Modified Albumin and decreased antioxidant values in relation to the inflammatory factors that were effective in the severe hyperemesis gravidarum group.